Pengaruh Kinerja Customer Service Import, Kinerja Pelabuhan dan Respon Billing DJBC (Direktorat Jendral Bea dan Cukai) Terhadap Kelancaran Pengeluaran Cargo di PT. Berdiri Matahari Logistik - Situmeang, Atika Hartari; Zaroni, Zaroni; Tatiana, Yana; Setiawan, Edhie Budi (Dinasti Research, 2025)
This study aims to analyze the impact of import customer service performance, port performance, and DJBC (Directorate General of Customs and Excise) billing response on the smoothness of cargo expedition at PT. Berdiri Matahari Logistik. The main issues identified include limited performance of customer service import, low port skills, and weak DJBC billing response, which affect the smoothness of cargo expedition. A quantitative method with a survey approach was used to collect data through questionnaires distributed to 102 service users in 2024. Data analysis was performed using SmartPLS 3 to test the structural equation model (SEM PLS). The results show that import customer service performance, port performance, and DJBC billing response have a significant positive impact on the smoothness of cargo expedition. It is recommended that PT. Berdiri Matahari Logistik improves customer service performance, provides ongoing training for service users, and implements a technology-based DJBC billing response system to enhance operational efficiency.